Praktyka dziedziczenia majątku przez kobiety w rodzinie chłopskiej na podstawie tekstów testamentów z drugiej połowy XVI i XVII stulecia - Świta, Amadeusz (Civitas et Lex, 2023)
The practice of women inheriting a property in 16th and 17th century peasant families was examined through an analysis of dozens of peasant wills. The problem addressed in the article – a micro-historical text – refers to peasant women living in different years in a number of villages located in, sensu lato, the Lesser Poland region (Polish: Małopolska). From the family histories shown in the texts of the last wills, it appears that a woman had the right to inherit, dispose of, and manage property. A young woman – a peasant’s daughter – received both movables (things of daily use) and real estate (buildings or pieces of land) as an inheritance (including a dowry). She could also advance, becoming heir to the entire farm. Despite these rights, in a broad sense, out of principle, the female peasants held lower position than their brothers. Dying peasants, however, valued their spouses – thanking them for their work and care, they often bequeathed all their possessions to them.